2022
DOI: 10.1002/jmv.28009
|View full text |Cite
|
Sign up to set email alerts
|

HPV‐CCDC106 integration promotes cervical cancer progression by facilitating the high expression of CCDC106 after HPV E6 splicing

Abstract: Human papillomavirus (HPV) integration and high expression of HPV oncogenes (E6 and E7) are important mechanisms for HPV carcinogenesis in cervical cancer. However, the relationship between HPV integration and HPV E6 spliced transcripts, as well as the underlying mechanisms of HPV integration in carcinogenesis after HPV E6 splicing remains unclear. We analyzed HPV‐coiled‐coil domain containing 106 (CCDC106) integration samples to characterize the roles of HPV integration, E6 spliceosome I (E6*I), and high CCDC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…To date, many studies have found that CCDC106 interacts with p53, resulting in p53 degradation in cancer cells and promoting cell proliferation 1,3,4,12 . In this work, we provide evidence that the C-terminal domain of the CCDC106 protein (CCDC106-CTD) directly interacts with the N-terminal domain of the p53 protein.…”
Section: Discussionmentioning
confidence: 99%
“…To date, many studies have found that CCDC106 interacts with p53, resulting in p53 degradation in cancer cells and promoting cell proliferation 1,3,4,12 . In this work, we provide evidence that the C-terminal domain of the CCDC106 protein (CCDC106-CTD) directly interacts with the N-terminal domain of the p53 protein.…”
Section: Discussionmentioning
confidence: 99%
“…Total proteins were obtained by lysing cells using RIPA lysis supplied with protease inhibitors (HY‐K0010, MCE). Equal quality proteins were then subjected to sodium dodecyl sulphate‐polyacrylamide gel electrophoresis (8012011, BioSci) gel electrophoresis and transferred onto polyvinylidene fluoride (PVDF) membrane (10600023, GE) at 4°C, respectively 30 . The PVDF membranes were incubated with 5% bovine serum albumin (Servicebio) and primary antibodies sequentially.…”
Section: Methodsmentioning
confidence: 99%
“…Equal quality proteins were then subjected to sodium dodecyl sulphatepolyacrylamide gel electrophoresis (8012011, BioSci) gel electrophoresis and transferred onto polyvinylidene fluoride (PVDF) membrane (10600023, GE) at 4°C, respectively. 30 The PVDF membranes were incubated with 5% bovine serum albumin (Servicebio) and primary antibodies sequentially. The details of primary antibodies were as follows: BaK…”
Section: Western Blottingmentioning
confidence: 99%
See 1 more Smart Citation
“…This depression of transcription and stabilization of fusion transcripts containing E6 and E7 synergistically intensify HPV oncogene expression 214 . Integrated tumors frequently manifest elevated levels of E6 splicing, such as E6*I 215 . Highly expressed HPV‐human fusion transcripts, such as HPV16 E6*I‐E7‐E1(SD880)‐human gene, drive cervical carcinogenesis, culminating in the overexpression of E6*I and E7 216 .…”
Section: Hpv and Its Pathogenesismentioning
confidence: 99%